A study on initiation of postpartum family planning in India based on NFHS-4: does urban poor differ significantly from rural? - Ujjaval Srivastava; Arvind Pandey; Pragya Singh; Kaushalendra Kumar Singh (BMC, 2022)
Abstract Objective To explore the differentials of postpartum contraceptive adoption between rural and urban poor after adjusting for utilization of MCH services and other selected socioeconomic and demographic covariates. Methods The data for this study is taken from the 4th round of NFHS survey conducted in India during 2015-16. The analysis is limited to 125,340 currently married women whose menses had returned at the time of survey. Discrete time complementary log-log multilevel model was applied.  Results The results clearly indicate that women from rural areas had a lower chance of early initiation of modern spacing methods after having recent birth as compare to that of Urban Poor and Urban non-poor areas. The contributions of several socioeconomic and demographic characteristics that were important for family planning practice were also highlighted in this study. Conclusion There is an urgent need of designing an intervention that will result in effective delivery of services to achieve the greatest impact. Policy planners must focus on targeted interventions for family planning use in the postpartum period than simply focusing on family planning.